If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 5y = -25 Solving -10x + 5y = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -10x + 5y + -5y = -25 + -5y Combine like terms: 5y + -5y = 0 -10x + 0 = -25 + -5y -10x = -25 + -5y Divide each side by '-10'. x = 2.5 + 0.5y Simplifying x = 2.5 + 0.5y
| 5w+37=2w+24 | | 24+x=40 | | -3t-7=-9 | | 2w+24=5w+37 | | w=11m | | 3(z-2)+26=5(z+4) | | 8x/76 | | 119+2h=909 | | 30+5y=8 | | 6-5h=7h-28 | | -10(x+5)+62=-149-19 | | 3(4z-1)-14= | | p(x)=6x^3-6x^2-14x-42 | | 8-(1/x) | | 8-y=25 | | y(2x-y-1)dx+x(2y-x-1)dy=0 | | y(2x-x-1)dx+x(2y-x-1)dy=0 | | tan(0.5x)=3 | | (2/3)*(-1/x)=2 | | -8x=72-16y | | 2b=7b-10 | | 3x-3y+9=0 | | 3x+2=729 | | (2-q)*q=-24 | | 3x^2y(5x+6y)= | | 1/8y=24 | | 2(7x-4)+3=5 | | y=6x^5-30x^4+18x^3-90x^2 | | 5x-2(4-x)=3x+20 | | 2(-4-4x)=-96 | | mx^2+2x+m=0 | | X=-4y-4Q |